Economic Value Added And Market Value Added At PT. Goto Gojek Tokopedia Tbk - Alfaini, Nur Risqi; Kholilah, Kholilah (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2023)
This research will ascertain PT GoTo Gojek Tokopedia's financial performance before the IPO. The NVivo 12 application is used to examine the qualitative research approach employed in this study. The findings revealed that EVA before the IPO was below zero, indicating that the company cannot add value for shareholders and cannot meet its debt obligations. In 2020, the MVA value was positive; in 2021, it was negative. According to these findings, the corporation did well in 2020 but poorly in 2021. These two findings show that the company's financial performance was poor before the IPO. As a result, the company's choice to go public was rushed and bad for stakeholders. This study is anticipated to offer stakeholders a reference method for measuring financial performance.